The Psychology of Study Success in Universities - Maatta, Kaarina; Uusiautti, Satu (Routledge, 2017)
Universities around the world are under increasing pressure to maintain high levels of graduation and to make study processes as efficient as possible, with teachers and students struggling to meet the expectations placed upon them as a result. The Psychology of Study Success in Universities asks whether it is possible to meet these demands at the same time as protecting the well-being of students. Drawing on an extensive and detailed analysis of study success in universities in Finland, the authors of this thought-provoking work argue that universities should be more concerned with students’ satisfaction and place greater weight on students’ perceptions of the elements that enhance or hinder their success. The book provides a multi-dimensional picture of the student-related and teaching-related factors that promote study success. Giving voice to graduate students, including those enrolled on a PhD, the authors look at the resources that students have at their disposal in order to establish what inspires and motivates the students, what slows them down, and what kinds of experiences students have of successful studies. Määttä and Uusiautti present a wealth of high-quality research showing that good teaching and successful study processes can be secured by immediate and caring interaction, flexible and student-centred teaching and supervision, and interdisciplinary collaboration between teachers. The Psychology of Study Success in Universities is essential reading for academics, researchers and postgraduate students in the fields of education and psychology, as well as for those interested in positive psychology, student well-being and pedagogical studies.